The Study of Motifs, Functions, and Philosophical Meanings of Maha Sri Bijawangsa Laut Tribe of Indragiri Hilir Regency - Yadona, Putri; Efi, Agusti; Haryono; Budiwirman; Elida (Indonesian Research Journal in Education |IRJE|, 2024)
This study aimed to analyze the motifs, functions, and philosophical meanings of the Maha Seribija Wangsa Songket of the Laut tribe. This study used a descriptive qualitative method with a cultural approach through document analysis, and the data analysis was performed using thematic analysis techniques. The results of the study are: (1) The Maha Seribija Wangsa Songket motif is a unified form consisting of the boat (Jalo), the compass point (Matu Meno), the anchor, the wave (Gelumbang), and the shell (Tengan) motif. The attributes of the Songket are the ladders, cross dice, service marks, Bengkong, and guide stick. (2) The functions of the Maha Seribija Songket of the Laut tribe leader include the coronation of the president, king, and sultan of the Laut tribe; the coronation of the vice president, ministers, patih, commander, laksmana, and formal ceremonies for the Laut tribe. (3) The philosophical meaning of the Maha Seribija Wangsa Songket includes the existence of the Laut tribe people in the middle of the sea and the coast, the direction of the Laut tribe in living their lives, the history of the Laut people who helped maintain the glory of the Malay Kings, the long, unbroken history of the Laut tribe people from the past until now, shellfish as the main livelihood of the Laut tribe people.